Psychological Distress, Social Stigma, Depression and Mental Health Crisis Among Nurses in High-Pressure Clinical Settings - Diah Priyantini; Erfan Rofiqi; Septian Galuh Winata; Chlara Yunita Prabawati; Dzakiyatul Fahmi Mumtaz; Ken Siwi; Annisa Wigati Rozifa; Daviq Ayatulloh; Nursalam Nursalam (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Nurses working in high-pressure clinical settings are frequently exposed to heavy workloads, emotional demands, and challenging working environments that may compromise their psychological well-being. Persistent occupational stress, combined with negative societal perceptions and stigma toward healthcare professionals, may contribute to psychological distress, depression, and broader mental health crises among nurses. Understanding the relationship between psychological distress and social stigma is essential to identify factors contributing to mental health problems in nursing professionals. Methods: A cross-sectional study was conducted between June and October 2021 involving 2,156 nurses working in high-pressure clinical units across Indonesia. Data were collected using an online questionnaire consisting of sociodemographic characteristics, measures of psychological distress, and social stigma perceptions, along with a modified Depression, Anxiety, and Stress Scale (DASS-21). A researcher-developed mental health crisis scale was also used to assess severe psychological conditions. Data were analyzed using descriptive statistics, Chi-square tests, and Spearman’s rho correlation with a significance level of p < 0.05. Results: Most participants were aged 20–29 years (44.6%) and female (67.5%). Psychological distress was reported at moderate levels among 78.4% of respondents, while 18.5% experienced perceived social stigma. Severe depression was identified in 64.5% of nurses, and 63.5% reported severe mental health crisis conditions. Psychological distress and perceived social stigma were significantly associated with higher levels of depression and mental health crises among nurses (p < 0.05). Conclusion: Psychological distress and social stigma were significant factors associated with depression and mental health crises among nurses working in high-pressure clinical environments. These findings highlight the importance of implementing institutional mental health support systems, stigma reduction initiatives, and workplace interventions to protect nurses’ psychological well-being.